Nipah virus encephalitis outbreak in Malaysia - Lam, Sai Kit; Chua, Kaw Bing (Oxford University Press, 2002)
Emerging infectious diseases involving zoonosis have become important global health problems. The 1998 outbreak of severe febrile encephalitis among pig farmers in Malaysia caused by a newly emergent paramyxovirus, Nipah virus, is a good example. This disease has the potential to spread to other countries through infected animals and can cause considerable economic loss. The clinical presentation includes segmental myoclonus, areflexia, hypertension, and tachycardia, and histologic evidence includes endothelial damage and vasculitis of the brain and other major organs. Magnetic resonance imaging has demonstrated the presence of discrete high-signal-intensity lesions disseminated throughout the brain. Nipah virus causes syncytial formation in Vero cells and is antigenically related to Hendra virus. The Island flying fox (Pteropus hypomelanus; the fruit bat) is a likely reservoir of this virus. The outbreak in Malaysia was controlled through the culling of >1 million pigs.